The influence of reverse flow within side branches on plaque formation relative to coronary bifurcation angles - Hyoung Gwon Choi; Duc Huynh Vo; Jung Yul Yoo; Sang Truong Ha; Kwan Yong Lee (Scientific Reports)
Abstract The occurrence of atherosclerotic lesions in the coronary bifurcation tends to progress confined to specific areas depending on blood flow patterns. We conducted a numerical investigation into the three-dimensional bifurcation flow of the coronary artery, focusing on a side branch vessel branching off at a specified bifurcation angle. This study examined the impact of the bifurcation angle on flow characteristics around the bifurcation region, including wall shear stress, static pressure, the size of the reverse flow zone, and the flow rate distribution to the side branch vessel. Unsteady pulsatile flow has been considered at Re = 300 assuming blood as a Newtonian fluid. Our numerical results indicate that as the bifurcation angle increases, the pressure drop between the inlet and outlet increases, while the flow rate to the side branch vessel decreases. Additionally, in our study, a reverse flow zone near the outer wall of the side branch was observed, and it was found that the reverse flow becomes stronger as the bifurcation angle increases due to the lower momentum of blood near the outer wall and the central part of the side branch vessel. The height of reverse flow zone of the side branch rapidly increases as the bifurcation angle increases up to about 60 degrees and then mildly saturates as the bifurcation angle increases. Flow stagnation in the reverse flow zone of the side branch may promote platelet aggregation and lipid deposition, accelerating the formation of atherosclerotic plaques.